(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Children with cleft lip and palate (CLP) require comprehensive treatment involving specialists from various disciplines: pediatricians, orthodontists, maxillofacial surgeons, otolaryngologists, speech-language pathologists, geneticists, and others (1, 4, 7, 13). In recent years, significant experience has been accumulated regarding the improvement of surgical methods for treating CLP; new types of surgical procedures have been developed, the approach to age-related indications for treatment has been modified, orthodontic care has been refined, and medical-genetic screening is being developed and implemented (Starikova N.B.). The importance and role of psychological and educational support for families raising children with congenital clefts have also increased. However, as noted by some authors, the existing literature primarily highlights the positive experiences associated with providing care to such children (9, 10).